2021
DOI: 10.1017/s0033291721000258
|View full text |Cite
|
Sign up to set email alerts
|

Prospective relationships of adolescents’ screen-based sedentary behaviour with depressive symptoms: the Millennium Cohort Study

Abstract: Background Frequent use of screen-based devices could be a modifiable risk factor for adolescent depression, but findings have been inconsistent and mostly from cross-sectional studies. We examined prospective associations of video gaming, social media, and internet use with depressive symptoms in adolescents. Methods A total of 11 341 adolescents from the Millennium Cohort Study, a representative, UK population-based. The main outcome was depressive symptoms from a Moods and Feelings Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 49 publications
4
19
0
6
Order By: Relevance
“…A study in Norway found that gaming use was associated with higher odds of symptoms of depression, although they used a 3 h cut-off compared with our 2 h cut-off and they did not investigate weekday versus weekend day differences [40]. On the other hand, similar to our findings, a meta-analysis (on all screen time) and a recent longitudinal study from the UK (on gaming specifically) reported that more frequent video gaming was associated with fewer depressive symptoms [41,42]. These findings highlight the need for more evidence directed at clarifying the relationship that gaming, and smartphone gaming, has (if any) with feelings of depression among youth both cross-sectionally and prospectively.…”
Section: Discussionsupporting
confidence: 67%
“…A study in Norway found that gaming use was associated with higher odds of symptoms of depression, although they used a 3 h cut-off compared with our 2 h cut-off and they did not investigate weekday versus weekend day differences [40]. On the other hand, similar to our findings, a meta-analysis (on all screen time) and a recent longitudinal study from the UK (on gaming specifically) reported that more frequent video gaming was associated with fewer depressive symptoms [41,42]. These findings highlight the need for more evidence directed at clarifying the relationship that gaming, and smartphone gaming, has (if any) with feelings of depression among youth both cross-sectionally and prospectively.…”
Section: Discussionsupporting
confidence: 67%
“…This aligns with previous findings that mentally-active sedentary behaviours do not necessarily increase the risk of depressive symptoms in adults and may reduce risk in some cases (18)(19)(20)(21). Several recent studies in adolescents have found association between some screen time modalities (e.g., watching television or using social media) and the risk of depression, but not video gaming (13,22), which may even have protective associations with mental health (25)(26)(27).…”
Section: Main Findingssupporting
confidence: 90%
“…Studies in adolescents have found that high social media, computer, or television use is associated with poorer mental health outcomes (13, [22][23][24], but not always video game use (13,22,25). Some studies have found protective associations between video gaming and mental health in adolescents (25)(26)(27). The factors underlying the relationship between screen time with mental health in adolescents can be complex (28,29), likely extend beyond the impacts of lower energy expenditure levels (30), and warrant a more nuanced investigation into different screen time modalities.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies reported no association between gaming and depressive symptoms [ 11 , 18 , 19 ]. Some other studies found a protective effect of video gaming on depression [ 36 ]. Moreover, using objective measures of video gaming a recent cross-sectional study found a positive relationship between video gaming and affective well-being [ 25 ].…”
Section: Discussionmentioning
confidence: 99%